2017
DOI: 10.15294/biosaintifika.v9i2.8907
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ethanolic Extract of Streptomyces sp. As a Pancreatic Lipase Inhibitors Produced by Endophytic Streptomyces sp. AEBg12

Abstract: Endophytic Streptomyces sp. AEBg12 isolated from Zingiber cassumunar (Bangle) is known to produce pancreatic lipase inhibitory compound. However, the characteristics of this active compound has not been reported yet. This study aimed to determine the characteristics of pancreatics inhibitory compound produced by Streptomyces sp. AEBg12 and to assess the role of endophytic actinobacteria in producing pancreatic lipase inhibitor using endophytic-free bangle tissue culture, wild bangle and compared with the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This shows that some of the ginger endophytic actinobacterial isolates have a higher ability to produce inhibitory values compared to their host plants (Figure 2). This result is in accordance with the study of pancreatic lipase inhibitors conducted by Fitri et al (2017b), where AEBg12 isolates from the bangle plant have higher pancreatic lipase inhibitors than their host plants. The resistance value of the AEBg12 isolate obtained was 95.6%.…”
Section: Activity Of Pancreatic Lipase Inhibitorssupporting
confidence: 91%
See 1 more Smart Citation
“…This shows that some of the ginger endophytic actinobacterial isolates have a higher ability to produce inhibitory values compared to their host plants (Figure 2). This result is in accordance with the study of pancreatic lipase inhibitors conducted by Fitri et al (2017b), where AEBg12 isolates from the bangle plant have higher pancreatic lipase inhibitors than their host plants. The resistance value of the AEBg12 isolate obtained was 95.6%.…”
Section: Activity Of Pancreatic Lipase Inhibitorssupporting
confidence: 91%
“…This is based on his research which contains pancreatic lipase inhibitors in gelugur acid (Garcinia atroviridis), galangal (Alpinia galanga) and kencur (Kaempferia galanga) which produce research on flavonoids. The results of the study by Fitri et al (2017b) also showed Streptomyces sp. AEBg12 from Bangle (Zingiber cassumunar) which produces pancreatic lipase inhibitors, produces a flavonoid composition in the three extracts distributed.…”
Section: Phytochemical Aj4 Isolatementioning
confidence: 84%
“…AEBg12 derived from the bangle plant contains flavonoids, saponins and steroids that act as pancreatic lipase inhibitors. Saponins have also been shown to inhibit lipase activity both in vitro and in vivo, so saponin compounds, steroids and flavonoids contained in kratom leaves are also thought to have the potential to be lipase inhibitors and play a role in the treatment of obesity (Fitri et al, 2017).…”
Section: Obesity Suppression With Lipase Inhibitorsmentioning
confidence: 99%
“…Aerial mycelium has a variety of colors, such as white, grey, red, green, blue, and purple. Fitri et al (2017), reported that isolates of endophytic actinobacteria grown on YMA medium produced grey, white, greenish grey, bluish grey, and turquoise aerial mycelium, while isolates grown on OA medium produced green, grey, white, and bluish green aerial mycelium.…”
Section: Morphological Characterization Of Actinobacteria Macroscopy ...mentioning
confidence: 99%